PENGARUH CAPITAL INTENSITY DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP TAX AVOIDANCE DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI - Syakirah, Alifah Hanif; Wawo, Andi; Anwar, Puspita Hardianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to determine the effect of Capital Intensity and Good Corporate Governance on Tax Avoidance with Corporate Social Responsibility (CSR) as a moderating variable in energy sector companies indexed on the Indonesian Sharia Stock Exchange. This study uses a quantitative approach with a comparative causal method and secondary data from company annual reports on the official IDX website and company websites. The population consists of energy sector companies listed on the IDX and indexed in the Indonesia Sharia Stock Index for the period 2019–2023. The sample was selected using purposive sampling, resulting in 21 companies with 105 observations over five years. Data analysis was conducted using multiple linear regression and moderation tests with SPSS Statistics 25. The results indicate that capital intensity has a positive effect on tax avoidance. Institutional ownership has no effect, while managerial ownership has a negative effect on tax avoidance. CSR does not moderate the relationship between capital intensity or institutional ownership and tax avoidance, but it strengthens the relationship between managerial ownership and tax avoidance.